INVESTIGATIONS ON THE EFFECT OF SODIUM TRIMETAPHOSPHATE AND SODIUM SULFATE CONCENTRATIONS ON THE PROPERTIES OF CROSS-LINKED CASSAVA STARCH FILMS - Marisa Ferreira Karow; Karine Laste Macagnan; Mariane Igansi Alves; Júlia Borin Fioravante; Rosane da Silva Rodrigues; Lígia Furlan; João Felipe Colosio de Souza; Claire Tondo Vendruscolo; Angelita da Silveira Moreira (Química Nova)
Films based on pure native starch have limited applications, are easily breakable, very hygroscopic, and permeable to water vapor. One method for improving these properties is to modify starch by cross-linking. The aim was to evaluate the effect of the addition of sodium trimetaphosphate (STMP), sodium sulfate (SS) and native cassava starch (S) on the properties of modified cassava starch films using a 23 factorial design comparing the concentration of the crosslinkers (5.0, 12.5 and 20% STMP), SS (3.0, 9.0 and 15%) and native cassava starch (S) (5.0, 7.5 and 10%) m/v. All cross-linked cassava starch films had better easiness of handling, continuity, and brightness than the control film. Generally, cross-linking reduced the water solubility and tensile strength and increased thickness, elongation and the films’ yellowish color and opacity. Reagents’ concentration affected most of the dependent variables. The SMTP*SS interaction positively affected water vapor permeability (WVP), while negatively affected solubility. Tensile strength was positively affected by SMTP. As for elongation, the S*SS interaction was positive, while the effect of STMP*SS was negative. Treatment 1, using the lowest concentrations of reagents, presented positive results, such as excellent macro and microscopic appearance. These findings also qualify the crosslinked starch for use in coatings formulations.